2022
DOI: 10.1159/000525337
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Angiotensin Ia Receptors in the Hypothalamic Paraventricular Nucleus Sensitize Neuroendocrine Vasopressin Release and Blood Pressure in a Rodent Model of Polycystic Kidney Disease

Abstract: Introduction: Angiotensin (Ang) II signalling in the hypothalamic paraventricular nucleus (PVN) via angiotensin type-1a receptors (AT1R) regulates vasopressin release and sympathetic nerve activity - two effectors of blood pressure regulation. We determined the cellular expression and function of AT1R in the PVN of a rodent model of polycystic kidney disease (PKD), the Lewis Polycystic Kidney (LPK) rat, to evaluate its contribution to blood pressure regulation and augmented vasopressin release in PKD. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…To assess the effects of 10 or 20 Hz stimulation of the dSC or dSC‐GiA terminals, systolic AP and rectified SNA were smoothed (1 s time constant), downsampled to 10 Hz and exported in contiguous blocks that started 20 s prior to and ended 30 s after the onset of stimulation; changes in systolic AP were expressed relative to the average baseline value; SNA was normalized relative to baseline (100%) and noise (0%: obtained by hexamethonium bromide at the conclusion of experiments: 5 mg i.v . (∼10 mg kg −1 ; Sigma Aldrich, Australia), as previously described (Underwood et al., 2022 ). Significant differences between responses to cl‐dSC stimulation in ChR2 and control animals, or between stimulation of cl‐dSC cell bodies or their GiA terminals, were identified by RM two‐way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the effects of 10 or 20 Hz stimulation of the dSC or dSC‐GiA terminals, systolic AP and rectified SNA were smoothed (1 s time constant), downsampled to 10 Hz and exported in contiguous blocks that started 20 s prior to and ended 30 s after the onset of stimulation; changes in systolic AP were expressed relative to the average baseline value; SNA was normalized relative to baseline (100%) and noise (0%: obtained by hexamethonium bromide at the conclusion of experiments: 5 mg i.v . (∼10 mg kg −1 ; Sigma Aldrich, Australia), as previously described (Underwood et al., 2022 ). Significant differences between responses to cl‐dSC stimulation in ChR2 and control animals, or between stimulation of cl‐dSC cell bodies or their GiA terminals, were identified by RM two‐way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the complex neurofunctional effects of the AT1R may emerge in interaction with other neural signaling systems, with recent evidence suggesting that interactions with the corticotrophin releasing hormone, dopaminergic, opioid, and vasopressin systems mediating AT1R regulation in some emotional and cognitive domains. The AT1R in the hypothalamic paraventricular nucleus (PVN) and the striatum critically regulate vasopressin 26 and dopamine (DA) release, 18,27 and its pharmacological blockade enhances DRD1 expression but decreases DRD3 sensitivity. 28 With respect to the functional interaction, it has been shown that mice with a deletion of the AT1R gene from corticotrophin releasing cells exhibited less freezing than wild-type mice during tests of conditioned fear expression, an effect that may be caused by a decrease in the consolidation of fear memory.…”
Section: Introductionmentioning
confidence: 99%